(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The process plants run 24/7 a year. Any disruption in the power supply can cause the process to halt, resulting in significant productivity loss and financial consequences. If the TANGEDCO main supply fails, the standby power should kick in without much delay. An Automatic Mains Failure (AMF) arrangement is necessary to satisfy this requirement, which automatically switches from utility to DG power in the event of utility power failure. An AMF arrangement was fabricated, wired up, interfaced with a laboratory three-phase alternator, and tested for various sequences as part of this project work. Interlocks and multiple operation sequences were also investigated in a real-time AMF circuit. The attached load information on the college campus was gathered, and the cable sizing was examined from the standpoint of generator activity. The generator was appropriately sized based on the load data obtained, the neutral arrangement was all checked, and proper sizing was arrived at to ensure stable operation of the Diesel Generator in standby mode of operation. The current continuous set mode of operation for DG sets with TANGEDCO supply is contrasted to the continuing HT conversion mode. Based on a comparative study, the economics of diesel consumption/TANGEDCO tariff is calculated. The proposed DG set’s positioning has also been optimized for greater service stability to feed the campus loads without disruption and to ensure effective operation. The proposed DG set’s location has also been optimized for greater versatility in service, to feed the campus loads without disruption and to ensure the DG set’s efficient operation. The entire function of the DG set is examined, taking into account all factors such as AMF, economics, operational stability, and so on.